Altered inhibitory modulation of somatosensory cortices in paroxysmal kinesigenic dyskinesia. Issue 12 (20th September 2013) - Hsu, Wan‐Yu; Kwan, Shang‐Yeong; Liao, Kwong‐Kum; Chen, Rou‐Shayn; Lin, Yung‐Yang
ABSTRACT Background The objective of this study was to clarify the excitability profiles of the somatosensory cortices in patients with paroxysmal kinesigenic dyskinesia. Methods Whole‐head magnetoencephalography was used to record the somatosensory evoked fields elicited by paired‐pulse electric stimulation of the median nerve in 15 patients with paroxysmal kinesigenic dyskinesia and in a control group of 18 age‐matched, healthy volunteers. Twelve of the patients were studied in both the drug‐off and drug‐on state. Results The paired‐pulse inhibition ratios of the primary somatosensory cortical P35m responses and the secondary somatosensory cortical responses were significantly greater in drug‐off patients with paroxysmal kinesigenic dyskinesia compared with either the drug‐on patients or the control group. No significant difference in paired‐pulse inhibition ratio was observed between the drug‐on patients with paroxysmal kinesigenic dyskinesia and the control group. Conclusions In patients with paroxysmal kinesigenic dyskinesia, intracortical inhibition of the primary and secondary somatosensory cortical areas is impaired, and the associated hyperexcitable phenomenon is modulatable by antiepileptic drugs. © 2013 International Parkinson and Movement Disorder Society